2012
DOI: 10.1002/ijc.27511
|View full text |Cite
|
Sign up to set email alerts
|

Immune response against Streptococcus gallolyticus in patients with adenomatous polyps in colon

Abstract: Our aim was to examine the humoral immune response against Streptococcus gallolyticus subspecies gallolyticus antigens in individuals subjected to a routine colonoscopy in which colon adenomatous polyps were present or not. Serum samples from 133 individuals with adenomatous polyps and serum samples from 53 individuals with a normal colonoscopy were included. Western blot was performed in all subjects using a whole cell antigen from S. gallolyticus ATCC 9809, and rabbit antisera against the whole cell bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…14 In the German case-control study, the SGG multiplex serology panel was extended to the 11 SGG proteins used in this study. 11,12,16,19 Here, we offer the first prospective observational evidence to support early involvement of SGG in colon carcinogenesis by showing that antibody responses to SGG were more frequently present in subjects who later developed CRC even more than two years after blood draw than those who remained disease-free during the same time-frame. Seropositivity for at least two proteins from a 6-marker panel subset (Gallo0272, Gallo0748, Gallo1675, Gallo2018, Gallo2178 and Gallo2179) was more specifically associated with CRC (19% SGG positives) compared to controls (11% of SGGpositives).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…14 In the German case-control study, the SGG multiplex serology panel was extended to the 11 SGG proteins used in this study. 11,12,16,19 Here, we offer the first prospective observational evidence to support early involvement of SGG in colon carcinogenesis by showing that antibody responses to SGG were more frequently present in subjects who later developed CRC even more than two years after blood draw than those who remained disease-free during the same time-frame. Seropositivity for at least two proteins from a 6-marker panel subset (Gallo0272, Gallo0748, Gallo1675, Gallo2018, Gallo2178 and Gallo2179) was more specifically associated with CRC (19% SGG positives) compared to controls (11% of SGGpositives).…”
Section: Discussionmentioning
confidence: 77%
“…In the 1970s, it was found that infective endocarditis What's new? [11][12][13][14] We previously applied multiplex serology, a fluorescent bead-based high-throughput technology allowing serological typing of several antigens in one reaction, 15 to analyze antibody responses to 11 SGG proteins in a German CRC casecontrol study. Here the authors performed a serological study in a prospective setting with samples from the European Prospective Investigation into Nutrition and Cancer (EPIC).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such antigen profiles of Sgg were found to be clearly associated with CRC already present at early polyp status suggesting early involvement of Sgg into the tumour environment (Tjalsma et al, 2006). Major protein antigens of Sgg were identified as HlpA and Rp L7/L12 (Boleij et al, 2010;Tjalsma et al, 2007;Tjalsma et al, 2006), in addition to two unidentified antigens of 22 and 30 kDa size (Garza-González et al, 2012), suggesting further potential for diagnostic tools to detect SBSEC.…”
Section: Invasion/translocation and Immune Response In Cell Culture Amentioning
confidence: 97%
“…is more frequently related to both endocarditis and colonic lesions than S. infantarius sp. (4,5). Nevertheless, S. infantarius sp.…”
mentioning
confidence: 99%